Documentação de software: uma análise comparativa entre documentação tradicional e living documentation - Silva, André Santiago da Fonseca (2020)
Many development teams that work with agile processes end up underestimating the importance of software documentation as a tool to support the scalability of their solutions and their production process. Failing to observe, according to agile values, that although software in operation is highly valued, having comprehensive documentation may also be necessary. In a development environment characterized by high employee turnover and diversity of solution domains, what we often observe are development teams trying to adapt Requirements Engineering activities and software documentation of the so-called traditional development processes. This situation can impact the developers’ understanding of the behavior of the software functionalities, reducing the competitive advantage of the agile development team. In this dissertation we quantify the impact that the software documentation has on the developers’ understanding regarding the behavior of the software functionalities. For this, through a controlled experiment, we made a comparative analysis between a type of software documentation characteristic of traditional development processes and the textit living documentation generated from the Oriented Development strategy to Behavior (from English textit Behavior Driven Development - BDD). The study came to the conclusion that, given the context in which it developed, traditional documentation seems to facilitate the understanding of the behavior of functionalities by developers, which indicates that the implementation of living documentation may have more of this challenge to be overcome implementation.